Decreased Levels of Fenol in the Case of Traditional Herb Industry using Anaerobic Activated Sludge Method - Sukma Budi Ariyani (Balai Riset dan Standardisasi Industri Pontianak, 2011)
Fenol is a hazardous substance that can pollute the environment. Traditional herb Industry is one of industries produces liquid waste with high pollution level, the fenol content more than 9 mg/L. Biological treatment with anaerobic activated sludge method is one effective way of processing waste.This research was aimed to study the effect of MLSS variable and fenol load, the efficiency of fenol decrease in anaerobic waste processing system. The experiment is conducted by synthetic herbs waste with COD content of ± 3610 mg/L, retention time of 6 hours at a temperature of 30oC, atmospheric pressure in anaerobic baffle reactor continuously. The reactor volume is 60 L, the MLSS content of 3000; 4000; 5000 mg/L, fenol load at 0, 3, 6; 9; 12 mg/L. Result of research show that active sludge of mixture breeding from cage manure effective for the processing of waste with the low rate fenol (less than 6 mg/L) with the efficiency of degradation fenol 89,7-99,87% but less be effective at high burden fenol (more than 6 mg/L) with the efficiency of degradation fenol equal to 18-52%. The results obtained compared well with other reduction process.